The Role of Parental Education in the Dental Health Behavior of Turkish Secondary School Children - Karaaslan Fatih (Balkan Journal of Dental Medicine, 2020)
Background/Aim: Parents are usually the major factor influencing children’s development of routine oral health behavior. A higher education level of the parents is generally associated with having a more positive influence on their children’s health habits and motivation to maintain healthy dentition. From this perspective, the aim of the present study was to investigate the frequency of certain habits influencing dental health, such as toothbrushing, regular visits to the dentist, and changing toothbrushes, in a group of Turkish secondary school children, and to explore its relation to the education level of their mothers and fathers.